2014
DOI: 10.1037/a0035959
|View full text |Cite
|
Sign up to set email alerts
|

Motherhood and oxytocin receptor genetic variation are associated with selective changes in electrocortical responses to infant facial expressions.

Abstract: Recent studies suggest that parental caregiving is associated with adaptive changes in neurocognitive responses to emotional cues and oxytocin function, possibly reflecting the increased need of parents to monitor infants’ emotional states. In the current study, we investigated whether the changes associated with motherhood and oxytocin receptor genetic variation rs53576 are specific to the processing of infant cues as opposed to a more general increase in responsiveness to emotional cues. We measured event-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 44 publications
(74 reference statements)
6
66
1
Order By: Relevance
“…Some studies reported no effect of valence on N170 responses [80,81]. However, another study demonstrated larger N170 amplitudes to negative compared to positive infant facial expressions during focused attention in both mothers and non-mothers, as well as a main effect of valence on latency of N170 responses [78]. For later EEG components, findings show greater concordance.…”
Section: Detailed Sensory Processing (N170 and Beyond)mentioning
confidence: 87%
See 3 more Smart Citations
“…Some studies reported no effect of valence on N170 responses [80,81]. However, another study demonstrated larger N170 amplitudes to negative compared to positive infant facial expressions during focused attention in both mothers and non-mothers, as well as a main effect of valence on latency of N170 responses [78]. For later EEG components, findings show greater concordance.…”
Section: Detailed Sensory Processing (N170 and Beyond)mentioning
confidence: 87%
“…One study has demonstrated a main effect of valence of infant facial expressions (happy, neutral, distressed) on the amplitude of N100 responses in both mothers and nulliparous women [78]. Other studies have reported no significant effect of valence on such early responses [79,80].…”
Section: Rapid Cortical Sensitivity: Modulation Of the N100mentioning
confidence: 97%
See 2 more Smart Citations
“…Consistent with ERP findings, RTs were significantly faster to evaluate negative emotional states compared to positive ones, with the fastest times in response to distress expressions. More recently, Peltola and colleagues (2014) replicated this ERP finding in a sample of women: the N170 amplitude in response to infant faces was larger to negative affective infant faces compared to positive affect across a sample of mothers and non-mothers.…”
Section: Neural Response To Infant Facesmentioning
confidence: 55%